Intestinal microbiota improves inflammation and cognitive function in the brain of a7nAChR deficient rat through the gut brain axis - Chi Cao; Shulin Li; Wencheng Wang; Lei Shi; Rui Ma; Bin Zhang; Jianying Tian (Scientific Reports)
Abstract To investigate the role of intestinal flora and cholinergic anti-inflammatory pathways in the gut-brain axis, using oral gavage and intraperitoneal injection of methyllycaconitine (MLA). MLA was administered at a dose of 4 mg/kg for 30 days, either orally or via intraperitoneal injection. Rats were then assessed for behavioral changes, inflammatory markers, neurotransmitters, neuroreceptors, and intestinal mucosal barrier integrity. Rats receiving MLA via intraperitoneal injection exhibited significant behavioral abnormalities compared to the control and orally administered MLA groups. The levels of IL-1β were elevated in both intestinal and hippocampal tissues, while IL-10 levels were decreased. Brain-derived neurotrophic factor (BDNF) was significantly lower in hippocampal tissues. Furthermore, α7nAChR expression was reduced in hippocampal tissues, accompanied by an increase in 5-HT3A receptors. The intestinal mucosal barrier was compromised, as evidenced by reduced expression of ZO-1 and Occludin, along with increased IL-1β and decreased IL-10 levels in the gut. Our findings suggest that oral gavage of MLA does not induce cognitive impairment in rats compared to intraperitoneal injection, possibly due to the involvement of intestinal flora in the protective effects of CAP.